Advanced Sorption Process Applications 2019
DOI: 10.5772/intechopen.80495
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Adsorption Kinetic Processes—Errors, Theory and Application

Abstract: Adsorption has become a competitive method in the field of wastewater and air treatment. Adsorption kinetics is one of the main factors that must be understood before the applicability of any adsorbent. In every adsorption process, linear or nonlinear analysis of the kinetics is applied. The goodness of fit index (coefficient of correlation or sum of squares) is applied to access the best model. The usage of linear or non-linear from of the adsorption kinetics has an impact on the distribution of error functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(98 citation statements)
references
References 68 publications
3
85
0
10
Order By: Relevance
“…As evident from the data analysis, the highest adsorption achieved using MnO 2 nanoparticles was at 750 °C annealing temperature. The adsorption data for all three models were statistically analyzed and it was found that pseudo-second order is the most suitable when the solute concentration is low (Kajjumba 2019). From Fig.…”
Section: Kinetic Adsorption Study Resultsmentioning
confidence: 99%
“…As evident from the data analysis, the highest adsorption achieved using MnO 2 nanoparticles was at 750 °C annealing temperature. The adsorption data for all three models were statistically analyzed and it was found that pseudo-second order is the most suitable when the solute concentration is low (Kajjumba 2019). From Fig.…”
Section: Kinetic Adsorption Study Resultsmentioning
confidence: 99%
“…In almost every adsorption study, linear shapes have been used to conclude the best kinetic/equilibrium model that influences the adsorption mechanism. This result can be a mistake because, in some instances, as found in some of our findings, even with some relatively high errors, the mathematical adjustments are superior for non-linear models, suggesting better adequacy of experimental data [101]. Many authors observed that non-linear models have a better fit to the experimental data, like Sahin and Tapadia [102], by evaluating fluoride adsorption onto a limonite geo-material,or like Markandeya et al [103], by evaluating disperse orange 25 dye on AC; or even like Can [104], by studying rhodium adsorption onto gallic acid derived polymer,or Moussout et al [81], which studied Cd 2+ adsorption onto chitosan (Cd 2+ /CS) and methyl orange onto bentonite (MO/Bt).…”
Section: Adsorption Equilibrium Studies and Comparison Between Linear And Non-linear Forms Of Isothermsmentioning
confidence: 57%
“…Boyd developed a model to understand whether film diffusion or intraparticle diffusion is the rate-controlling step in adsorption kinetics. 31 This model is based on the assumption that the boundary layer on the adsorbent surface has a significant effect on the diffusion of a gas. This effect is determined as followsHere, F is the fraction of CO 2 gas adsorbed at time t ( q t ) to CO 2 gas adsorbed at an infinite time, that is, at equilibrium ( q e ).…”
Section: Methodsmentioning
confidence: 99%